Transcranial direct current stimulation for Obsessive-Compulsive Disorder: An examination of treatment effectiveness and acceptability. - Green, Peta Evelyn (Curtin University, 2024)
This thesis explored the effectiveness and acceptability of transcranial direct current stimulation for obsessive-compulsive disorder. A systematic review identified that the quality of trial reporting and design in this area needs improvement. In a world-first case series combining tDCS with traditional exposure and response prevention for treatment-refractory OCD, clinically significant change was initially observed, supporting the continued investigation of this dual protocol approach. A need for longer-term maintenance protocols, to retain treatment gains, was identified.